Exploring Possible Relations Between Optical Variability Time Scales and Broad Emission Line Shapes in AGN - Bon, Edi; Jovanović, Predrag; Marziani, Paola; Bon, Nataša; Otašević, Aleksandar (Frontiers in Astronomy and Space Sciences, 2018)
Here we investigate the connection of broad emission line shapes and continuum light curve variability time scales of type-1 Active Galactic Nuclei (AGN). We developed a new model to describe optical broad emission lines as an accretion disk model of a line profile with additional ring emission. We connect ring radii with orbital time scales derived from optical light curves, and using Kepler's third law, we calculate mass of central supermassive black hole (SMBH). The obtained results for central black hole masses are in a good agreement with other methods. This indicates that the variability time scales of AGN may not be stochastic, but rather connected to the orbital time scales which depend on the central SMBH mass.